2022
DOI: 10.1038/s41598-022-07995-7
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA and metagenomic shotgun sequencing data revealed consistent patterns of gut microbiome signature in pediatric ulcerative colitis

Abstract: Dysbiosis of human gut microbiota has been reported in association with ulcerative colitis (UC) in both children and adults using either 16S rRNA gene or shotgun sequencing data. However, these studies used either 16S rRNA or metagenomic shotgun sequencing but not both. We sequenced feces samples from 19 pediatric UC and 23 healthy children ages between 7 to 21 years using both 16S rRNA and metagenomic shotgun sequencing. The samples were analyzed using three different types of data: 16S rRNA genus level abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…Notably, Veillonella parvula , E. coli , R. gnavus and Clostridium clostridioforme were significantly enriched species in CD compared with UC and healthy controls, while F. prausnitzii is the most depleted species in CD. Interestingly, Zuo et al 44 . demonstrated that although the 16s data shows similar results as shotgun sequencing data in terms of alpha diversity and beta diversity, 16S genus data (AUC = 0.869) achieved higher pediatric UC prediction performance than shotgun species data (AUC = 0.763) and pathway data (AUC = 0.764).…”
Section: Role Of Gut Microbiome In Ibd Diagnosismentioning
confidence: 98%
See 2 more Smart Citations
“…Notably, Veillonella parvula , E. coli , R. gnavus and Clostridium clostridioforme were significantly enriched species in CD compared with UC and healthy controls, while F. prausnitzii is the most depleted species in CD. Interestingly, Zuo et al 44 . demonstrated that although the 16s data shows similar results as shotgun sequencing data in terms of alpha diversity and beta diversity, 16S genus data (AUC = 0.869) achieved higher pediatric UC prediction performance than shotgun species data (AUC = 0.763) and pathway data (AUC = 0.764).…”
Section: Role Of Gut Microbiome In Ibd Diagnosismentioning
confidence: 98%
“…Interestingly, Zuo et al. 44 demonstrated that although the 16s data shows similar results as shotgun sequencing data in terms of alpha diversity and beta diversity, 16S genus data (AUC = 0.869) achieved higher pediatric UC prediction performance than shotgun species data (AUC = 0.763) and pathway data (AUC = 0.764).…”
Section: Role Of Gut Microbiome In Ibd Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The human gut microbiome, the microbial communities inhabiting our gastrointestinal tract, can greatly influence human health through the immune and metabolic systems ( Holmes et al., 2012 ). Many studies have demonstrated the complicated associations between gut microbiome and human diseases such as inflammatory bowel disease (IBD) ( Norman et al., 2015 ; Zuo et al., 2022 ), metabolic diseases ( Qin et al., 2012 ) and autoimmune diseases ( Tomofuji et al., 2022 ). The human gut microbiome, which could be altered by some of the mentioned risk factors, has also been considered as one of the most important environmental factors in the development of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…With the development and availability of new technologies based on genetic sequencing, it is possible to quickly characterize, identify and quantify millions of genomic sequences. Metagenomic studies, although complex, have been used successfully in different contexts and/or applications, such as medicine, animal production, pharmacological, polluted ecosystems, soils, and water, among others, which is undoubtedly increasing the accumulated knowledge about the bacterial microbiota, its interactions with the environment and other microorganisms [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%